The Effect of Mobile Learning on Critical Thinking Skills of Early Childhood Education Teacher Prospective Students: Meta-Analysis 2021-2024 - Panggabean, Tongam E; Rizki, Sofan; Walid, Abul; Yanti, Dawi; Agustina, Ika; Wariunsora, Marlen; Mas’ud, Abdurahman; Santosa, Tomi Apra (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2024)
Many previous studies have reported that there are many different impacts of the application of mobile learning in improving students' critical thinking skills. This study aims to determine the effect of mobile learning on critical thinking skills in early childhood teacher candidates through meta-analysis. In this study, 27 studies that met the inclusion criteria were analyzed. The inclusion criteria in this study are 1) the research was published in 2021-2024; 2) the research must be relevant; 3) research must be reputable indexed by SINTA or Scopus; 4) The research must report complete data. The data was analyzed using Excel and JASP applications by presenting the results of effect size, funnel plot, and publication bias. The results of the analysis concluded that mobile learning had a positive influence on the critical thinking ability of prospective early childhood education teachers compared to other learning (g = 1.204; 95% CI 1.007; 1.401; p < 0.001). (This finding informs that mobile learning is effective in improving the critical thinking skills of prospective early childhood education teachers.